Activated RIC, a small GTPase, genetically interacts with the Ras pathway and calmodulin during Drosophila development. - Harrison, S.M.; Rudolph, J.L.; Spencer, M.L.; Wes, P.D.; Montell, C.; Andres, D.A.; Harrison, D.A. (Developmental Dynamics, 2005)
The mammalian Rit and Rin proteins, along with the Drosophila homologue RIC, comprise a distinct and evolutionarily conserved subfamily of Ras-related small GTP-binding proteins. Unlike other Ras superfamily members, these proteins lack a signal for prenylation, contain a conserved but distinct effector domain, and, in the case of Rin and RIC, contain calmodulin-binding domains. To address the physiological role of this Ras subfamily in vivo, activated forms of the Drosophila Ric gene were introduced into flies. Expression of activated RIC proteins altered the development of well-characterized adult structures, including wing veins and photoreceptors of the compound eye. The effects of activated RIC could be mitigated by a reduction in dosage of several genes in the Drosophila Ras cascade, including Son of sevenless (Sos), Dsor (MEK), rolled (MAPK), and Ras itself. On the other hand, reduction of calmodulin exacerbated the defects caused by activated RIC, thus providing the first functional evidence for interaction of these molecules. We conclude that the activation of the Ras cascade may be an important in vivo requisite to the transduction of signals through RIC and that the binding of calmodulin to RIC may negatively regulate this small GTPase.